PERTANGGUNGJAWABAN TINDAK PIDANA KORUPSI DANA DESA OLEH PANGULU NAGORI (DESA) NAGORI DESA PEMATANG SINAMAN (Studi Putusan PN. Tipikor Nomor 67/Pid.Sus.TPK/2019/ PN.Mdn) - Ramces Pandiangan; Marlina Marlina; Nelvitia Purba (LPPM YPITI, 2021)
Misuse cases that occur in village fund management are carried out in various modus operandi, such as drafting a budget fee above the market price then paying based on another agreement, temporarily borrowing village funds by transferring funds to a personal account and then not returning it. The formulation of the problem in this thesis is how the deviation of village funds by Nagori leaders in Pematang Sinaman village related to village funds in 2015 in Simalungun Regency, North Sumatra Province, how are the accountability of the perpetrators of corruption in village funds in PN decisions. Tipikor No.67 / Pid.Sus.TPK / 2019 / PN.Mdn, what is the basis for the judge's consideration of the decision against the defendant in the PN decision. Tipikor No.67 / Pid.Sus.TPK / 2019 / PN.Mdn. The research method used is descriptive analysis which leads to normative juridical legal research, namely research carried out by referring to legal norms, namely examining library materials or secondary materials. Secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. The results showed that the deviation of village funds by Nagori leaders in Pematang Sinaman village related to village funds in 2015 in Simalungun Regency, North Sumatra Province was the Village Fund Budget that had been disbursed by the defendant Darma Suardi as the Head of Tanah Besih Village together with Muhammad Noor as Treasurer of Tanah Besih Village. However, in carrying out activities using village funds, other village officials were not involved. The accountability of perpetrators of corruption in village funds in PN decisions. Tipikor No.67 / Pid.Sus.TPK / 2019 / PN.Mdn is Darma Suardi sentenced to prison for 6 (six) years and a fine of Rp. 200,000,000, - (two hundred million rupiah). in the District Court decision. Tipikor No.67 / Pid.Sus.TPK / 2019 / PN.Mdn is the defendant's actions in accordance with the legal facts revealed in court and there is no justification or excuse.